Assessing reading 1 : theory and practice. International perspective on reading assessment (London ; New York : Routledge, 1998)
Responsive reading assessment. Ten dilemmas of performance assessment. Feminist poststructuralist perspectives on the language of reading assessment...
Keywords: Reading; Reading -- Ability testing; Educational tests and measurements